2015
DOI: 10.1073/pnas.1505917112
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 exerts oncogenic activities through enhancing Yes-associated protein stability

Abstract: Yes-associated protein (YAP), a transcription coactivator, is the major downstream effector of the Hippo pathway, which plays a critical role in organ size control and cancer development. However, how YAP is regulated by extracellular stimuli in tumorigenesis remains incompletely understood. Netrin-1, a laminin-related secreted protein, displays proto-oncogenic activity in cancers. Nonetheless, the downstream signaling mediating its oncogenic effects is not well defined.Here we show that netrin-1 via its trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 32 publications
(32 reference statements)
3
33
2
Order By: Relevance
“…49 Our studies suggest that neogenin/RhoA/ YAP/Smad1 signaling plays a critical role in BMP2-induced astrocyte differentiation of NSCs. Although netrin-1 via DCC receptor up-regulates YAP expression, escalating YAP levels in the nucleus and promoting cancer cell proliferation and migration, 50 our results showed that netrin-1 did not regulate YAP level in WT or neogenin mutant astrocytes. Further investigation is necessary to illustrate whether neogenin/RhoA/YAP/Smad1 signaling pathway is involved in BMPs-induced differentiation of GICs, which may reveal novel therapeutic targets for astroglioma.…”
contrasting
confidence: 61%
“…49 Our studies suggest that neogenin/RhoA/ YAP/Smad1 signaling plays a critical role in BMP2-induced astrocyte differentiation of NSCs. Although netrin-1 via DCC receptor up-regulates YAP expression, escalating YAP levels in the nucleus and promoting cancer cell proliferation and migration, 50 our results showed that netrin-1 did not regulate YAP level in WT or neogenin mutant astrocytes. Further investigation is necessary to illustrate whether neogenin/RhoA/YAP/Smad1 signaling pathway is involved in BMPs-induced differentiation of GICs, which may reveal novel therapeutic targets for astroglioma.…”
contrasting
confidence: 61%
“…As a consequence, combining conventional drugs and netrin-1 interference increases tumor cell death in vitro and potentiates tumor growth inhibiting effect in vivo, thus suggesting that, even when tumors do not express high levels of netrin-1, a combination of conventional drugs plus drugs inhibiting netrin-1-receptors interaction could amplify the chemotherapy-induced response. As discussed above, netrin-1 may not only have a pro-oncogenic effect by blocking the death induced by DCC or UNC5H, it may also activate "protumorigenic" pathways, as recently shown by the implication of the YAP pathway (38), thus further strengthening the rationale for moving netrin-1 interference into the clinic. A humanized monoclonal antibody disrupting netrin-1-receptors interaction is under preclinical development, with a clinical phase I scheduled for early 2016.…”
Section: A Novel Therapeutic Approach?mentioning
confidence: 72%
“…Because PP1A may dephosphorylate YAP primarily on S397 (Qi et al, 2015), we tested whether PP1A binding to YAP was diminished upon Cdc42 deletion. To that end, we performed co-immunoprecipitation of YAP and PP1A and found a significant reduction in pulled-down PP1A (but not PP2A, data not shown) in Cdc42 cKO laCL lysates (Figure 6J).…”
Section: Resultsmentioning
confidence: 99%